THE BAD DEBT DEDUCTION OF SAVINGS AND LOAN ASSOCIATIONS. - Spencer, Charles H. (The Accounting Review, 1956)
Savings and loan associations are permitted to deduct, under Sec. 593 of the Internal Revenue Code of 1954, any amount they choose as additions to reserves for bad debts, so long as those amounts do not bring theft total reserves, surplus, and undivided profits accounts to more than 12 per cent of savings capital. This provision is in direct contradiction to established accounting theory, which holds that deductions for bad debts should be estimated in relation to the risk assets owned as part of the process of matching costs and revenues of any given period, so that the net income of that period may be determined. Even though the savings and loan industry is apparently suffering no current tax pain, a longer-range look at Sec. 593 should provide a sobering view for the associations. Competitors and opponents of the associations may argue that Sec. 593 is a tax-avoidance device, giving the associations an unfair tax advantage. The tremendous growth of the savings and loan business since the removal of tax exemption in 1951 has permitted the great majority of the associations to add to their reserves with an almost complete disregard for the income tax factor. Thus the provision could lead to much more onerous and burdensome taxation being imposed upon the associations. Another danger in the reserve provision is the likelihood that the 12 per cent level set by the law for tax-free building of reserves will have the effect of a ceiling upon efforts to build reserves, even though much higher reserves may be needed. It is extremely difficult to predict what level of reserves may be necessary for any given association, and it is dangerous to think in terms of a stipulated reserve level which may be applied to the entire savings and loan industry. Finally, the provisions of Sec. 593 are dangerous to associations in periods of economic tension because, as savings and more liquid assets might contract sharply, continued deductions for reserves would be desirable, but they perhaps could be provided only by paying the penalty of corporate income taxation, whereas in prosperous times, no tax need be paid. Thus, at the time the institutions might most need liquidity, their stability and solvency would be most threatened by taxation. The provisions of Sec. 593 may prove very harmful if they induce the associations to modify their business behavior solely in order to minimize their corporate income taxes. It would appear that, since the bad debt deduction is one which applies for nearly all accrual basis taxpayers-not savings and loan associations alone -before net income may be computed, the amount of the deduction is essentially an accounting problem and should be computed according to accounting principles applying to the determination of net income.